Comparing Age- and Grade-Based Norms on the Woodcock–Johnson III Normative Update. (October 2019) - Harrison, Allyson G.; Butt, Kaitlyn; Armstrong, Irene
There has been a marked increase in accommodation requests from students with disabilities at both the postsecondary education level and on high-stakes examinations. As such, accurate identification and quantification of normative impairment is essential for equitable provision of accommodations. Considerable diversity currently exists in methods used to diagnose learning disabilities, including whether an impairment is normative or relative. This study investigated the impact on impairment classification if grade-based norms were used to interpret identical raw scores compared with age-based norms. Fourteen raw scores distributed equally across the adult range of the Woodcock–Johnson III Normative Update subtests were scored using norms for either age (18-29 years) or grade (13-17). The results indicate that raw scores receive a significantly lower standardized score (and thus percentile ranking) when grade-based norms are used. Furthermore, the difference between age- and grade-based scores increases dramatically as raw scores decrease, and there is a significant interaction between age and grade in the standard scores obtained. This study provides evidence to suggest that using different norms may result in different decisions about diagnoses and appropriate accommodations.